Acidentes de trânsito em Belo Horizonte: fatores associados ao atendimento pré-hospitalar, internações e óbitos em 1994 e 2003 - Roberto Marini Ladeira (2007)
Traffic accidents victim care is a challenge for health services, claiming for complex systems able to deliver appropriate care. Two main services in this system are prehospital and hospital care. This thesis, presented by way of two scientific articles, looked into socio-demographiccharacteristics, type of care, severity and outcomes of traffic accidents victims admitted at hospitals in Belo Horizonte, Southeast Brazil. The data were obtained from two longitudinal studies carried out by Belo Horizonte Municipal Health Authority and Transportation and Traffic Office of Belo Horizonte (BHTRANS) in 1994 and 2003. In both studies, the patients were followed up for 90 days or death, if it occurred before the end of follow up. The first article, based in the 2003 study, has investigated the factors associated with the use of pre-hospital care service (PHCS) in a sub-group of victims whose accident has occurred in Belo Horizonte. This analysis was restricted to 2003 because pre-hospital care service was not available in 1994. Among 1564 victims, 49.7% was transported by the pre-hospital care service to hospitals. The use of PHCS was greater among victims with more severe injuries (AIS=2 and AIS.3), older victims (30-39 years, 40-49 years, .50 years), those who reported alcohol use, and those with time between accident and hospital admittance inferior to 60 minutes. The use of PHCS was lower among bicycle occupants andpedestrians. The second article presents a comparison of socio -demographic, accidents, type of care characteristics and outcomes between the two studies (1994 and 2003). Important changes occurred between the two year-periods: implementation of the new BrazilianTraffic Code, creation of the pre-hospital care service and a skyrocketing increase in the number of motorized vehicles, especially motorcycles.The number of victims was 1719 in 1994 and 2272 in 2003. In both studies, the majority of victims were young men. There was a fall in the number of more severely injured victims (14.5% vs 9.2%) and a significant rising of motorcycle occupants (12.2 vs. 32.8%). In 1994, prevalence of hospitalization was higher among men, victims with more severe injuries, with older age and who reported alcohol use. Multivariate analysis showed that hospitalization prevalence was associated with injuries severity. In 2003, in multivariate analysis, injuries severity and bicycle occupants were associated with hospitalizations. In 1994, injury severity and older age were associated with death in survival analysis. In2003, survival analysis also showed that injury severity and older age were associated with death up to 90 days after accident. Results showed that the pre-hospital care service was responsible for the transportationto hospital of approximately half of the victims and that PHCS was more common among victims with more severe injuries and with lower time of arrival to hospital. Although is not possible to define what measure really works, we found a change in victims profile, a reduction in severity of injuries and case fatality rate. Results points out the need of continuing monitoring the factors associated with hospitalizations, deaths and trends in morbidity and mortality of traffic accidents.